Plasma Small Extracellular Vesicles Derived miR-21-5p and miR-92a-3p as Potential Biomarkers for Hepatocellular Carcinoma Screening - Sorop, Andrei; Iacob, Razvan; Iacob, Speranta; Constantinescu, Diana; Chitoiu, Leona; Fertig, Tudor Emanuel; Dinischiotu, Anca; Chivu-Economescu, Mihaela; Bacalbasa, Nicolae; Savu, Lorand; Gheorghe, Liliana; Dima, Simona; et al. (Frontiers in Genetics, 2020)
Introduction Liquid biopsy using circulating microvesicles and exosomes is emerging as a new diagnostic tool that could improve hepatocellular carcinoma (HCC) early diagnosis and screening protocols. Our study aimed to investigate the utility of plasma exosomal miR-21-5p and miR-92-3p for HCC diagnosis during screening protocols. Methods The study group included 106 subjects: 48 patients diagnosed with HCC during screening, who underwent a potentially curative treatment (surgical resection or liver transplantation), 38 patients with liver cirrhosis (LC) on the waiting list for liver transplantation, and 20 healthy volunteers. The exosomes were isolated by precipitation with a reagent based on polyethylene glycol and were characterized based on morphological aspects (i.e., diameter); molecular weight; CD63, CD9, and CD81 protein markers; and exosomal miR-21-5p and miR-92a-3p expression levels. Results We first demonstrate that the exosome population isolated with the commercially available Total Exosome Isolation kit respects the same size ranging, morphological, and protein expression aspects compared to the traditional ultracentrifugation technique. The analysis of the expression profile indicates that miR-21-5p was upregulated (p = 0.017), and miR-92a-3p was downregulated (p = 0.0005) in plasma-derived exosomes from HCC subjects, independently from the patient’s characteristics. AUROC for HCC diagnosis based on AFP (alpha-fetoprotein) was 0.72. By integrating AFP and the relative expression of exosomal miR-21-5p and miR-92a-3p in a logistic regression equation for HCC diagnosis, the combined AUROC of the new exosomal miR HCC score was 0.85—significantly better than serum AFP alone (p = 0.0007). Conclusion Together with serum AFP, plasma exosomal miR-21-5p and miR-92a-3p could be used as potential biomarkers for HCC diagnosis in patients with LC subjected to screening and surveillance.